2009
DOI: 10.3945/ajcn.2009.27462v
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the gut-brain axis by dietary glutamate and physiologic significance in energy homeostasis

Abstract: l-Glutamate is a multifunctional amino acid involved in taste perception, intermediary metabolism, and excitatory neurotransmission. In addition, recent studies have uncovered new roles for l-glutamate in gut-brain axis activation and energy homeostasis. l-Glutamate receptors and their cellular transduction molecules have recently been identified in gut epithelial cells. Stimulation of such l-glutamate receptors by luminal l-glutamate activates vagal afferent nerve fibers and then parts of the brain that are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 80 publications
0
54
0
4
Order By: Relevance
“…By coupling to this pathway, sensing of glutamate at the oral umami receptors could possibly be a signal to the body that protein-rich food is on the way. The feedback to the brain along the gut-brain axis is a signal of satiety and satisfaction [32]. In this way, umami taste sensed at the taste buds at the tongue may facilitate the body's alertness to be ready to digest the food and regulate appetite and food intake.…”
Section: The Flavor Of Food Under Siegementioning
confidence: 99%
“…By coupling to this pathway, sensing of glutamate at the oral umami receptors could possibly be a signal to the body that protein-rich food is on the way. The feedback to the brain along the gut-brain axis is a signal of satiety and satisfaction [32]. In this way, umami taste sensed at the taste buds at the tongue may facilitate the body's alertness to be ready to digest the food and regulate appetite and food intake.…”
Section: The Flavor Of Food Under Siegementioning
confidence: 99%
“…L-Glutamate is present as a free amino acid in various food products such as seaweed, soya sauce, fermented beans, an extract made from beef meat, aged cheeses, cured ham and tomatoes. Thus, it is unlikely that free glutamate is a major taste marker of dietary protein to the individual (42,55) . Satiation feedback signals originating from the stomach are the result of volumetric signals produced by mechanoreceptors (56) .…”
Section: Detection Of Protein and Amino Acids During Digestion And Comentioning
confidence: 99%
“…Our primary goal was to examine whether intestinal administration of physiological concentrations of different taste stimuli sensed by taste receptors located in the upper gastrointestinal tract leads to signals that are conducted to and processed by the central nervous system and would evoke different blood-oxygendependent (BOLD) response during working memory processing. While studies on rats have been carried out and demonstrated activation of forebrain regions in functional MRI in response to intragastric infusions of taste solutions [6,7] no previous trials -to the best of our knowledge -examined human gastrointestinal taste receptor stimulation and afferences to the central nervous system by functional brain MRI. ) were analyzed.…”
Section: Introductionmentioning
confidence: 99%